2006
DOI: 10.3354/ame042075
|View full text |Cite
|
Sign up to set email alerts
|

Modelled effects of ambient UV radiation on a natural Antarctic marine microbial community

Abstract: Ozone depletion over Antarctica has enhanced ultraviolet-B radiation (UVBR, 280 to 320 nm wavelength). We measured the effect of ambient solar UV radiation on the biomass and species composition of phytoplankton, protozoa, bacteria and dissolved organic carbon (DOC) in natural microbial assemblages from Antarctic coastal waters. Results were modelled to determine the features of the irradiance responsible for changes in the biomass of these microbial components and responses of individual phytoplankton taxa. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Limited evidence suggests this alters the balance between UV-B-induced photodamage and PAR-and UV-A-induced repair (Smith et al 1992, Vincent & Roy 1993, Holm-Hansen et al 1997. Furthermore, our finding of significant inhibition of protist taxa by UV-B radiation in January agrees with a modelling study by Nunez et al (2006) that showed changes in the structure and function of a diatomdominated community at Davis Station below an ozone threshold of 300 DU. However, our use of a broadband sensor to measure erythemal UV radiation precluded our ability to detect changes in the ratio of UV-B radiation to other wavelengths.…”
Section: Januarysupporting
confidence: 91%
“…Limited evidence suggests this alters the balance between UV-B-induced photodamage and PAR-and UV-A-induced repair (Smith et al 1992, Vincent & Roy 1993, Holm-Hansen et al 1997. Furthermore, our finding of significant inhibition of protist taxa by UV-B radiation in January agrees with a modelling study by Nunez et al (2006) that showed changes in the structure and function of a diatomdominated community at Davis Station below an ozone threshold of 300 DU. However, our use of a broadband sensor to measure erythemal UV radiation precluded our ability to detect changes in the ratio of UV-B radiation to other wavelengths.…”
Section: Januarysupporting
confidence: 91%
“…The few available experiments carried out with natural phytoplankton populations grown under UVR ambient conditions also demonstrate growth inhibition (Davidson & Belbin 2002, Nunez et al 2006. Here we show that ambient UVR not only suppresses Antarctic phytoplankton growth but also induces important cell death.…”
Section: Discussionmentioning
confidence: 79%
“…Although sufficient irradiance is essential for phytoplankton to grow, mesocosm experiments conducted with natural coastal Antarctic plankton (Agustí et al 2009) showed that Antarctic phytoplankton communities are either light limited or light stressed when exposed to high irradiances, suggesting the role of UVR as a potential inhibitor of phytoplankton growth and biomass (Agustí et al 2009). There have been only few studies examining the impact of increased UVBR levels on the growth of Antarctic phytoplankton populations in situ, with most studies performed with isolated Antarctic phytoplankton growing in cultures and exposed to artificial light (Davidson et al 1994, Davidson & Belbin 2002, Nunez et al 2006. Moreover, the effect of UVR on phytoplankton cell mortality has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Concern about global environmental changes, especially the increase in UV-B radiation due to ozone depletion, makes it necessary to study stress physiology on primary producers. In Antarctica, research efforts to evaluate the impact of this phenomenon have mostly focused on phytoplankton (Meador et al 2002;Nunez et al 2006). However, phytoplankton does not represent the only significant photoautotroph component of the aquatic environment susceptible to elevated UV-B.…”
Section: Introductionmentioning
confidence: 99%